2007
DOI: 10.1583/1545-1550(2007)14[460:svblsf]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Sirolimus-Eluting Versus Bare-Metal Low-Profile Stent for Renal Artery Treatment (GREAT Trial): Angiographic Follow-up After 6 Months and Clinical Outcome up to 2 years

Abstract: The angiographic outcome at 6 months did not show a significant difference between BMS and SES. Renal artery stenting with both stents significantly improved blood pressure. Future studies with a larger patient population and longer angiographic follow-up are warranted to determine if there is a significant benefit of drug-eluting stents in treating ostial renal artery stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
28
0
3

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 17 publications
2
28
0
3
Order By: Relevance
“…The United States multicenter trial found no beneficial effect of 3-month warfarin treatment after the procedure. 23 Four comparative studies showed no improvement in restenosis rate and clinical outcome with gold-, carbon-or sirolimus-coated stents [19][20][21][22] (Table III).…”
Section: Benefit Of Renal Artery Stenting Over Angioplastymentioning
confidence: 99%
“…The United States multicenter trial found no beneficial effect of 3-month warfarin treatment after the procedure. 23 Four comparative studies showed no improvement in restenosis rate and clinical outcome with gold-, carbon-or sirolimus-coated stents [19][20][21][22] (Table III).…”
Section: Benefit Of Renal Artery Stenting Over Angioplastymentioning
confidence: 99%
“…Mit schwerwiegenderen prozedurbedingten Komplikationen wie akutem Nierenversagen, Niereninfarkt, perirenalem Hämatom und thrombotischem Nierenarterienverschluss muss in 9% der Fälle gerechnet werden [28]. Keine Vorteile scheinen hingegen beschichtete Stents im Vergleich zu unbeschichteten Stents zu haben [53].…”
Section: Interventionelle Therapieunclassified
“…Im Rahmen der GRE ATStudie wurde der Effekt von mit Si rolimus beschichteten Stents prospektiv, nicht randomisiert, nichtgeblindet und multizentrisch untersucht. Nach 6 Mona ten konnte weder in Bezug auf die Offen heitsrate, noch in Bezug auf den Blutdru ckeffekt ein signifikanter Unterschied zu nicht beschichteten Stents festgestellt wer den [76].…”
Section: Beschichtete Stentsunclassified